Implementation of Islamic Religious Education in Madrasah Ibtidaiyah During Covid-19 Pandemic - Sartika, Fitria; Ritonga, Mahyudin; Rasyid, Aguswan (Khalifa Journal of Islamic Education, 2020)
The research of this article aims to find out and analyze the implementation of Islamic Religious Education learning in Madrasah Ibtidaiyah during the Covid-19 pandemic.Â  The research method used is qualitative research with a case study approach. The primary data source was obtained through interviews with three Islamic Religious Education teachers at Tarbiyah Islamiyah Private Madrasah Ibtidaiyah Koto Panjang Lampasi Payakumbuh, Indonesia. Interviews are conducted individually. Secondary data obtained from various pieces of literature in the form of books and articles. The results of this study show that there are two ways that Islamic Religious Education teachers use in carrying out learning in Madrasah Ibtidaiyah during the Covid-19 pandemic, namely online and offline based. Online-based learning by utilizing the Parents' WhatsApp Group (WAG). Offline is carried out for students whose parents do not have a smartphone, by requesting and delivering tasks directly to Islamic Religious Education teachers in madrasahs. From the research, it can be concluded that Islamic Religious Education teachers are required to be able to make the most of technology in learning, and all obstacles must be provided solutions according to the needs of students.